Multifunctional copper dimer: structure, band gap energy, catalysis, magnetism, oxygen reduction reaction and proton conductivity - Sarkar, D.; Chandra Rao, P.; Aiyappa, H. B.; Kurungot, S.; Mandal, S.; Ramanujam, K.; Mandal, S. (RSC Advances, 2016)
A new dimeric copper complex namely, [Cu2(PDA)2(Ald)2(H2O)2]·8H2O, 1, (where PDA = 2,4-pyridine dicarboxylic acid, Ald = aldrithiol) has been synthesized through a slow diffusion technique. Compound 1 is a molecular structure and assembled through H-bonding forming a supramolecular architecture. The CuO2N3 units bridged through an aldrithiol molecule to form the dimeric structure. The lattice water molecules are linked through H-bonding to form the decameric water cluster. The decameric water clusters are H-bonded to each other to form the 1D chain which resulted in excellent water stability and conduction of protons under humid conditions. Band gap energy and magnetic measurements show that compound 1 is a semiconductor and paramagnetic in nature. Further the compound is shown as a selective heterogeneous catalyst for styrene and cyclohexene epoxidation. This also shows a facile oxygen reduction reaction (ORR) and can be used as a promising Pt-free cathode in alkaline Direct Methanol Fuel Cells (DMFC). The present results suggest that compound 1 is a promising multifunctional material

Synthesis, antitubercular and antimicrobial potential of some new thiazole substituted thiosemicarbazide derivatives - Abhale, Y. K.; Shinde, A.; Deshmukh, K. K.; Nawale, L.; Sarkar, D.; Mhaske, P. C. (Medicinal Chemistry Research, 2017)
The increase in antibiotic resistance due to multiple factors has warranted the need for the search of new compounds which are active against multidrug resistant pathogens. In this context a small focused library of thiosemicarbazide derivatives of 2-arylthiazole-4-carbaldehyde, 4-methyl-2-arylthiazole-5-carbaldehyde and 1-(4-methyl-2-arylthiazol-5-yl) ethanone, (5a–l) has been synthesized. The title compounds were screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis Bacille Calmette Guerin (ATCC 35743) strains. The synthesized compounds, 5a–l were further assayed for their cytotoxic activity against the two human cancer cell lines, HeLa and human colon carcinoma 116 cell lines and showed no significant cytotoxic activity against these two cell lines at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bacteria, Escherichia coli, Pseudomonas flurescence and Gram-positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderate activity against fungal strain Candida albicans. This study provides valuable directions to our ongoing endeavor of rationally designing more potent antimycobacterial agent. © 2017, Springer Science+Business Media, LLC.
Keywords: Antimicrobial activity; Antitubercular activit; Cytotoxicity; Thiazole; Thiosemicarbazide

Dicationic liquid mediated synthesis of tetrazoloquinolinyl methoxy phenyl 4-thiazolidinones and their antibacterial and antitubercular evaluation - Deshmukh, A. R.; Dhumal, S. T.; Nawale, L. U.; Khedkar, V. M.; Sarkar, D.; Mane, R. A. (Synthetic Communications, 2019)
In a search of new potentially active antitubercular agents here we have synthesized 3-substituted phenyl-2-(4-(tetrazolo[1,5-a]quinolin-4-ylmethoxy)phenyl)thiazolidin-4-ones (8a–l) and evaluated their antibacterial, particularly antitubercular activity. These have been conveniently synthesized by performing one–pot cyclocondensation of 4-(tetrazolo[1,5-a]quinolin-4-ylmethoxy)benzaldehyde, anilines and mercaptoacetic acid in dicationic ionic liquid, (3-methyl-1-[3-(methyl-1H-imidazolium-1-yl)propyl]-1H-imidazolium dibromide [C3(MIM)2–2Br]) and obtained excellent yields of (8a–l). 4-Thiazolidinones (8a–l) were thoroughly characterized by their spectral analyses. These compounds have been screened for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra and Mycobacterium bovis (BCG). The compounds 8a, 8c, and 8e exhibited notable in vitro antitubercular activity compare to the reference, Rifampicin. Molecular docking study has also been performed to know the binding mode of these analogs in to the active site of DprE1 enzyme. The synthesized compounds were also evaluated for their in vitro antibacterial activity and amongst them compound 8k has shown moderate activity against both gram-negative and gram-positive bacterial strains.

Microwave‐assisted synthesis and antituberculosis screening of Some 4‐((3‐(trifluoromethyl)‐5,6‐dihydro‐[1,2,4]triazolo[4,3‐a]pyrazin‐7(8H)‐l)methyl)benzenamine hybrids - Patil, Y.; Shingare, R.; Choudhari, A.; Sarkar, D.; Madje, B. (Journal of Heterocyclic Chemistry, 2019)
In the present investigation, a series of 4‐((3‐(trifluoromethyl)‐5,6‐dihydro‐[1,2,4]triazolo[4,3‐a]pyrazin‐7(8H)‐yl)methyl)benzenamine analogs 6a–o were synthesized and characterized by IR, NMR (1H and 13C), and mass spectra. All newly synthesized compounds 6a–o were prepared under conventional and microwave irradiation methods. These compounds obtained in higher yields and in shorter reaction times in the microwave irradiation method when compared with the conventional method. Synthesized compounds 6a–o were inspected for their in vitro antitubercular activity against Mycobacterium tuberculosis H37Ra using an established XTT reduction menadione assay. Among the screened compounds, 6i (IC50: 1.82 μg/mL), 6j (IC50: 1.02 μg/mL), and 6k (IC50: 1.59 μg/mL) showed excellent activity. Furthermore, compound 6i showed MIC90 value of 16.02 μg/mL. In summary, the results indicate the identification of some novel, selective, and specific inhibitors against M. tuberculosis that can be explored further for the potential antitubercular drug.